Cytomegalovirus-associated transverse myelitis: A review of nine well-documented cases - Arslan, Ferhat; Yılmaz, Mesut; Paksoy, Yahya; Karagöz, Ergenekon; Mert, Ali (Taylor and Francis, 2015)
Cytomegalovirus-associated transverse myelitis is a rare disease. We found 12 cases in the medical literature, 8 of which met our criteria for being well documented. Our aim was to review this clinical entity using information from our own clinical experience as well as published cases.
WOS: 000350052400002
PubMed ID: 25390688
Keywords: Cytomegalovirus; Myelitis